Staging democracy : political performance in Ukraine, Russia, and beyond - Pisano, Jessica (NIU series in Slavic, East European, and Eurasian studies., 2022)
"This book analyzes twenty-first century performances of democratic politics in Ukraine and Russia. The study goes backstage at rigged elections, protests for hire, and smaller scale mises en scène to explain why people participate, the role of economic change, and how political theater alters the meaning of politics" --